2022
DOI: 10.48550/arxiv.2203.15402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physics-informed deep-learning applications to experimental fluid mechanics

Abstract: High-resolution reconstruction of flow-field data from low-resolution and noisy measurements is of interest due to the prevalence of such problems in experimental fluid mechanics, where the measurement data are in general sparse, incomplete and noisy. Deep-learning approaches have been shown suitable for such super-resolution tasks. However, a high number of high-resolution examples is needed, which may not be available for many cases. Moreover, the obtained predictions may lack in complying with the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A similar study using PINNs for velocity-field reconstruction from sparse data can be found in [27]. Another application of PINNs was presented by Eivazi et al [3] and Eivazi et al [4,5], who applied the PINN algorithm to solve the Reynolds-averaged-Navier-Stokes (RANS) for incompressible ZPGTBLs without any prior assumptions for turbulence. Along with supervised learning from the domain boundary, mean-flow quantities and their coordinates at the domain boundary were used as input data.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A similar study using PINNs for velocity-field reconstruction from sparse data can be found in [27]. Another application of PINNs was presented by Eivazi et al [3] and Eivazi et al [4,5], who applied the PINN algorithm to solve the Reynolds-averaged-Navier-Stokes (RANS) for incompressible ZPGTBLs without any prior assumptions for turbulence. Along with supervised learning from the domain boundary, mean-flow quantities and their coordinates at the domain boundary were used as input data.…”
Section: Introductionmentioning
confidence: 92%
“…Note that the laws governing fluid-dynamics problems are non-linear partial differential equations (PDEs). Eivazi and Vinuesa [5] showed the potential of using PINNs to reconstruct experimental data with noise and other measurement errors, including vortical flows and wall-bounded turbulence. A similar study using PINNs for velocity-field reconstruction from sparse data can be found in [27].…”
Section: Introductionmentioning
confidence: 99%
“…A similar PINN-based framework was also applied to the problem of super-resolution, i.e. inferring higher resolution flow features from low resolution ones in space and time 31,32 . It was shown that the PINN could reconstruct the higher resolution flow characteristics in space and time for a series of canonical non-reacting flows both from simulation data 31 or from experimental data 32 .…”
Section: Introductionmentioning
confidence: 99%
“…inferring higher resolution flow features from low resolution ones in space and time 31,32 . It was shown that the PINN could reconstruct the higher resolution flow characteristics in space and time for a series of canonical non-reacting flows both from simulation data 31 or from experimental data 32 . Therefore, the HFM approach has only been applied to flows of constant density or small density variations that can be described by a Boussinesq approximation.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this paper is to examine some of the ML tools that have been applied with promising results to reconstruct data from incomplete observations of complex systems, including idealized turbulent [34][35][36][37][38][39][40][41], engineering [42][43][44][45], and geophysical flows [32,33], and to discuss the possible future directions for quantitative advancements in fluid mechanics.…”
mentioning
confidence: 99%